Les « gestes d’atmosphère » au cœur de l’éthique relationnelle. L’ajustement médecins-patients lors de la consultation pré-anesthésique - Dominique Broussal (Questions Vives)
This contribution aims to test the model of professional gestures in the context of pre-anaesthetic consultations. The investigation carried out by the doctor requires the cooperation of the patient. The patient has important information about his lifestyle, his level of anxiety and his relationship with pain. The doctor must therefore establish a favourable relational climate. In this article, we have focused precisely on the analysis of concerns relating to the relational climate, based on the observation made by Bucheton (2019) that the gestures relating to it are at the heart of relational ethics. The results confirm that doctors and patients are equally concerned about maintaining an atmosphere favourable to exchanges.